THE USE OF SURGICAL PRACTICE IN WOMEN OF REPRODUCTIVE AGE WITH SEVERE DEGREES OF GENITAL PROLAPSE - Shavkatov Xasan Shavkatovich (Web of Journals Publishing, 2024)
In the article, the analysis of organ-preserving surgery performed on women of reproductive age is studied. Under our examination, 48 patients with III-IV level of prolapse of the genital organs encountered in our women were divided into their ages from 25 to 39 years of age. All methods of examination in our patients have been uttered IE general clinical-laboratory and gynecological examinations. The causes of genital prolapse have been studied and analyzed while the Anamnesis of patients under our examination has been thoroughly analyzed.
Keywords: Sexual prolapse, reproductive age, transvaginal hysterectomy, cystocele, rectocele.